One new and two unknown species of free - living marine nematodes from Can Gio mangrove forest, Ho Chi Minh city, Vietnam - Quang, Ngo Xuan; Thanh, Nguyen Vu; Chau, Nguyen Ngoc; Smol, Nic; Vanreusel, Ann (Academia Journal of Biology, 2014)
One new and two unknown species of free living marine nematodes belonging to family Oxystominidae are described from Cangio mangrove forest, Hochiminh city of Vietnam. The Oxystomina paraclavicaudata sp. nov. is characterized by the long conico-cylindrical tail with claviform tip, the double parallel spicules and the pre-and postvulval papillae. The species Litinium sp1. can be recognized by labial setae and cephalic setae follow the structure 6 + 6 + 4; amphid pear-shaped with slit-like aperture; spicules have a kink at the middle; gubernaculum short, plate-like; two papilliform supplements with short seta; tail rounded with the pore of caudal glands at the end. And Litinium sp2. is characterized by labial setae small or absent, two subcephalic setae at the posterior edge of the amphid; amphid elongate pocket-like with a fringe around the aperture; only one short somatic setae at the base of pharynx. Reproductive system diorchic with short testes; two supplement setae; only two caudal gland cells observed within the tail, the opening is shifted ventrally.